Studi Efektivitas Penerapan Kurikulum Merdeka Belajar di SMA Islam Athirah 1 Makassar - Yusran Yusran; Markani Markani (Jurnal Syntax Admiration, 2024)
This research aims to analyze and also develop the effectiveness of implementing the curriculum they study at SMA Islam Athirah 1 Makassar. The independent learning curriculum is a new policy in the world of education in Indonesia which gives freedom to each educational unit in managing and developing a curriculum that suits the needs and characteristics of students. By taking this approach, we will explore the opinions of each student teacher and also the school principal regarding the implementation of the independent learning curriculum at SMA Islam Athirah 1 Makassar. The data collected in this article was through observation and interviews. The independent learning curriculum at SMA Islam Athirah 1 Makassar will have a positive impact in increasing creativity, independence and interest in learning for students at SMA Islam Athirah 1 Makassar.